(untitled) (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2026)
The airways are divided into the upper and lower respiratory tract, depending on their location in the body. The upper respiratory tract includes the nasal cavity, the nasal and oral part of the khalkum, the lower respiratory tract include the hiccups, trachea (throat), bronchi, and lungs. It has a tubular structure characteristic of its activity, keeping its cavity at the same level as it is a bone and a humerus in the respiratory wall. The inner surface of the respiratory tract contains glands that synthesize a slime substance consisting of a mucous membrane, the surface of which is covered with a hovering epithelium. Therefore, the mucous membrane, in combination with its protective function, purifies the air and, warming up, humidifies the air in the airway.